Steganographic scheme to avoid statistical Steganalysis (Journal of the College of Education for Women, 2019)
significant bits either in the spatial domain or frequency domain sequentially or pseudorandomly through the cover media (Based on this fact) statistical Steganalysis use differenttechniques to detect the hidden message, A proposed method is suggested of a stenographicscheme a hidden message is embedded through the second least significant bits in thefrequency domain of the cover media to avoid detection of the hidden message through theknown statistical Steganalysis techniques.